Maulid-i šarīf-i Šahīd - Šahīd, Ġulām Imām ((Rājah) Rām Kumār Pres vāris̱-i Naval Kišor Pres Lakhnaʾū, 1953)
Devotional poetry in praise of the Prophet Muhammad, along with prose excerpts from his biography